2015
DOI: 10.1007/s00330-015-3911-0
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar annulus fibrosus biomechanical characterization in healthy children by ultrasound shear wave elastography

Abstract: Objectives Intervertebral disc (IVD) is key to spine biomechanics, and it is often involved in the cascade leading to spinal deformities such as idiopathic scoliosis, especially during the growth spurt. Recent progress in elastographic techniques allowed access to noninvasively measure cervical IVD in adults; the aim of this study was to determine the feasibility and reliability of shear wave elastography in healthy children lumbar IVD.Methods Elastographic measurements were performed in thirty-one healthy chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 30 publications
4
29
1
Order By: Relevance
“…US elastography is increasingly used for the diagnosis of stiffness in numerous circumscribed tissues [1,[4][5][6][7][8][9][10][11][12][13][14][15][16][17]. To date, there has been a lack of phantom studies which have systematically assessed the current US shear wave elastography techniques (pSWE with fixed ROI vs. 2D-SWE with variable ROI) in an effort to evaluate their suitability/test performance for this condition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…US elastography is increasingly used for the diagnosis of stiffness in numerous circumscribed tissues [1,[4][5][6][7][8][9][10][11][12][13][14][15][16][17]. To date, there has been a lack of phantom studies which have systematically assessed the current US shear wave elastography techniques (pSWE with fixed ROI vs. 2D-SWE with variable ROI) in an effort to evaluate their suitability/test performance for this condition.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the measurement procedure in the second part of the study was repeated five times for each target type, with the stiffness value defined as the mean of the five measurements for each ROI diameter (diameters: 40, 38, 36, 34,32,30,28,26,24,22,20,18,16,14,12,10,8,6, 4 and 2 mm).…”
Section: Study Design -Measurement Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…SWS was measured in all included subjects following a previously described protocol for lumbar IVD of adolescents [25]. Measurements were performed with an Aixplorer (SuperSonic Imagine, France) and a superlinear Sl 10-2 probe.…”
Section: Ivd Sws Acquisition Protocolmentioning
confidence: 99%
“…Those authors showed correlations between SWS and the mechanical properties of IVD, as well as in vivo reliability both in children and adults. A standardized, reproducible protocol was determined for the acquisition and processing of images for lumbar AF in healthy children and adolescents [25]. Measurements in scoliotic patients, however, are still lacking.…”
Section: Introductionmentioning
confidence: 99%